Role of bilateral corticobulbar tracts in dysphagia after middle cerebral artery stroke. (11th July 2020) - Im, S.; Han, Y.J.; Kim, S.‐H.; Yoon, M.‐J.; Oh, J.; Kim, Y.
Abstract: Background and purpose: The corticobulbar tract is a potential neural pathway involved in swallowing. The frontal operculum, insular cortex, corona radiata and internal capsule, which are frequently involved in middle cerebral artery (MCA) strokes, are locations in which lesions cause dysphagia. However, it is unclear whether the locations are linked to the corticobulbar tract or whether corticobulbar tract integrity is associated with dysphagia severity. This study aimed to assess the association between corticobulbar tract integrity and dysphagia severity after MCA stroke. Methods: Thirty dysphagic patients after MCA stroke and 27 healthy controls were examined. Diffusion tensor imaging (DTI)‐derived parameters of the corticobulbar tract were compared between patient and control groups. Next, patients were divided into mild and moderate‐to‐severe dysphagia groups, and DTI‐derived parameters of the corticobulbar tract were compared between the subgroups. Logistic regression analysis was used to determine the association between corticobulbar tract integrity and dysphagia severity. Results: The tract volume (TV) of the affected corticobulbar tract was lower in dysphagic patients than in healthy controls ( P < 0.001). According to dysphagia severity, TV of the unaffected corticobulbar tract was higher in the mild dysphagia group than in the moderate‐to‐severe dysphagia group ( P = 0.012). TV of the unaffected corticobulbar tract was independently associated with dysphagia severity according to the logistic regression model (adjusted odds ratio 0.817, 95% confidence interval 0.683–0.976). Conclusions: The corticobulbar tract was affected after MCA stroke and may be associated with dysphagia. A higher corticobulbar TV in the unaffected hemisphere was indicative of better swallowing function in dysphagic patients after MCA stroke.